Targeting p38 MAP kinase signaling in cancer through post-translational modifications - Zou, Xiao; Blank, Michael (Cancer letters, 2017)
The p38 MAPK signaling pathway is a key signal transduction cascade that cancer cells employ to sense and adapt to a plethora of environmental stimuli, and has attracted much attention as a promising target for cancer therapy. Accumulating evidence suggests a dual role of p38 signaling in various types of cancers, wherein the p38 pathway can both suppress and promote tumor growth, metastasis and chemoresistance. This dual role of p38 signaling, along with its context dependence and versatility, poses a great challenge for developing efficient anticancer treatment. An increasing number of studies showed that p38 signaling is subject to regulation by a variety of post-translational modifications (PTMs). Recently, large-scale proteomics profilings have identified a large number of PTMs on key components of the p38 pathway. However, the majority of these modifications and their biological significance in cancer remain uncharacterized. In this review, we highlight a series of studies that focus on the PTMs in the p38 cascade landscape, and discuss the complexity and implications of these PTMs in p38 MAPK signaling regulation. •p38 MAPK signaling is a major organizer of cellular response to external stimuli.•Accumulating evidence suggests a dual role of p38 MAPK signaling in cancer.•More PTMs in the p38 signaling landscape are being increasingly unveiled.•Deeper insights into PTMs and their impact on p38 signaling in cancer are needed.